الموضوعاتية وآليات إنتاج الدلالة -دراسة في قصص أحمد رضا حوحو- - طيهار نسيبة, مشرفا ومقررا أ.د نور الدين سيليني (My University, 2021)
الملخص: الموضوعاتية وآليات إنتاج الدلالة دراسة في قصص "أحمد رضا حوحو" عرضنا في الفصلين النظريين أهم المراحل التاريخية التي مر بها النقد الموضوعاتي من خلال حضور البنيوية الموضوعاتية المتحكمة في النص الأدبي، حيث وضعناها ضمن مخطط موضوعاتي ذو أعمدة صاعدة ونازلة وموضوعاتية من خلال مجموعتين قصيتين هما: "صاحبة الوحي، ونماذج بشرية" لأحمد رضا حوحو بطريقة إحصائية ريشارية وتبينا أن الحافز الموضوعاتي هو النفاق الاجتماعي الذي تكمن من نفوس بعض البشر وتكمن منها. وكما تتبعنا في الفصل التطبيقي حضور الموضوعة من خلال حضور تيمة الظلم، وتيمة الحب، وتيمة المرأة وتيمة الحسد وتيمة الألم على أساس التيمات الأكثر إرتباطا بالموضوعة الرئيسية وهي الفسد. Abstract: Thematic and Production Mechanisms of Meaning A study in the stories of "Ahmed Reda Houhou" In the two theoretical chapters, we presented the most important historical stages of the thematic criticism through the presence of the thematic structuralism that controls the literary text, where we put it within a thematic scheme which is ascending, descending and thematic columns through two different stories entitled: “The Revelator” and “Human Models” by Ahmed Rédha Houhou, in statistical method of Jean-Pierre Richard, it has shown that the thematic motive is the social hypocrisy that has been able to reincarnate some human beings. Moreover, in the practical study, we traced the topic by attending the themes of injustice, love, women, envy, and pain. On the basis of the most closely related themes to the main topic which is corruption. Keywords: thematic criticism, thematism, mechanisms, production of meaning, Ahmed Reda Houhou, the author of the revelation, human models, Thematic statistic
Keywords: الكلمات المفتاحية: النقد الموضوعاتي، الموضوعاتية، آليات، إنتاج الدلالة، أحمد رضا حوحو، صاحبة الوحي، نماذج بشرية، الإحصائية الموضوعاتية